Tumor treating fields in combination with gemcitabine or gemcitabine plus nab-paclitaxel in pancreatic cancer: Results of the PANOVA phase 2 study - Rivera, Fernando; Benavides, Manuel; Gallego, Javier; Guillen-Ponce, Carmen; Lopez-Martin, José; Küng, Marc (Pancreatology : official journal of the International Association of Pancreatology (IAP) ... [et al.], 2019)
Tumor Treating Fields (TTFields), low intensity alternating electric fields with antimitotic activity, have demonstrated survival benefit in patients with glioblastoma. This phase 2 PANOVA study was conducted to examine the combination of TTFields plus chemotherapy in patients with pancreatic ductal adenocarcinoma (PDAC). Forty patients with newly-diagnosed, locally advanced or metastatic PDAC received continuous TTFields (150 KHz for ≥18 h/day) plus gemcitabine (1000 mg/m2), or gemcitabine plus nab-paclitaxel (125 mg/m2). The primary endpoint was safety and secondary endpoints included compliance to TTFields, progression-free survival (PFS), and overall survival (OS). Seventeen patients (85%) in each cohort reported Grade ≥3 adverse events (AEs). No increase in serious AEs (SAEs) was observed compared to that anticipated with systemic chemotherapy alone. Twenty-one patients reported TTFields-related skin toxicity, of which 7 were Grade 3; all resolved following temporary reduction of daily TTFields usage. No TTFields-related SAEs were reported. Compliance to TTFields was 68–78% of the recommended average daily use in both cohorts. Median PFS was 8.3 months (95% CI 4.3, 10.3) and median OS was 14.9 months (95% CI 6.2, NA) in the TTFields + gemcitabine cohort. In the TTFields + gemcitabine + nab-paclitaxel cohort, the median PFS was 12.7 months (95% CI 5.4, NA); median OS has not been reached. The PANOVA trial demonstrated that the combination of TTFields and systemic chemotherapy is safe and tolerable in patients with advanced PDAC. Based on the safety and preliminary efficacy results of this phase 2 study, a randomized phase 3 study (PANOVA-3) is underway.